Active material, electrode, secondary battery, battery pack, and vehicle

By using secondary particles containing multiple primary particles containing niobium oxide as the negative active material, the problems of low energy density and short life of secondary batteries during rapid charge and discharge are solved, and high output performance and excellent life performance are achieved. of battery.

CN119340383APending Publication Date: 2025-01-21KK TOSHIBA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410225969.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-07-21
Filing Date
2024-02-29
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

In the process of fast charging and discharging, existing secondary batteries have problems of low energy density and short life, especially when using titanium oxide as the negative electrode material, the electrode potential is high and the capacity per unit weight is low.

Method used

Secondary particles containing a plurality of primary particles containing niobium oxide are used as the negative electrode active material. The secondary particles include adjacent parts where the primary particles are adjacent to each other and a constriction part where the primary particles are joined to each other. By adjusting the primary particles The ratio of the total circumference to the circumference of the primary particles outside the constriction portion improves the diffusibility and electronic conductivity of lithium ions.

Benefits of technology

A secondary battery with high output performance and excellent life performance has been realized, and the diffusivity and electronic conductivity of lithium ions have been improved to extend the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119340383A_ABST
    Figure CN119340383A_ABST
Patent Text Reader

Abstract

The embodiment of the invention relates to an active material, an electrode, a secondary battery, a battery pack, and a vehicle. Provided are an active material and an electrode capable of realizing a secondary battery having high output performance and excellent life performance, a secondary battery and a battery pack having high output performance and excellent life performance, and a vehicle provided with the battery pack. According to an embodiment, there is provided an active material including secondary particles including a plurality of primary particles including a niobium-containing oxide. The secondary particles include an adjacent portion in which the primary particles are adjacent to each other and a constricted portion in which the primary particles are joined to each other. The total circumferential length L of the primary particles and the sum Lcl of the circumferential lengths of the primary particles excluding the necking portion satisfy the relationship 0.1 < (L-Lcl) / L < = 0.6.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] Embodiments of the present invention relate to an active material, an electrode, a secondary battery, a battery pack, and a vehicle. Background Art

[0002] In recent years, as high energy density batteries, research and development of secondary batteries such as non-aqueous electrolyte secondary batteries such as lithium ion secondary batteries are being actively carried out. Secondary batteries such as non-aqueous electrolyte secondary batteries are expected to be used as power sources for vehicles such as hybrid electric vehicles and electric vehicles, and uninterruptible power supplies for mobile phone base stations. Therefore, in addition to being required to have high energy density, secondary batteries are also required to have other excellent properties such as fast charge and discharge performance and long-term reliability. For example, a secondary battery that can be quickly charged and discharged not only greatly shortens the charging time, but also improves the power performance of vehicles such as hybrid electric vehicles and makes it possible to effectively recover the regenerated energy of the power.

[0003] In order to enable rapid charge and discharge, electrons and lithium ions must be able to move quickly between the positive and negative electrodes. However, if a battery using a carbon-based negative electrode is repeatedly charged and discharged rapidly, dendrites of metallic lithium will form on the electrode, which may cause heat and fire due to internal short circuits.

[0004] Therefore, batteries using metal composite oxides instead of carbonaceous materials in the negative electrode have been developed. Among them, batteries using titanium oxide in the negative electrode have the performance of being able to perform stable rapid charge and discharge and having a longer life than batteries using carbon-based negative electrodes.

[0005] However, titanium oxide has a higher potential relative to metallic lithium than carbonaceous materials, that is, it is expensive. In addition, the capacity per unit weight of titanium oxide is low. Therefore, batteries using titanium oxide in the negative electrode have a problem of low energy density.

[0006] For example, the electrode potential of titanium oxide is about 1.5 V (vs. Li / Li + ), which is higher (more expensive) than the carbon-based negative electrode. The potential of titanium oxide is due to the fact that Ti is electrochemically inserted and released by lithium. 3+ With Ti 4+ The redox reaction between Li and Li is therefore restricted electrochemically. + ) is the fact that lithium ions can be stably charged and discharged rapidly at a high electrode potential of about 100 Å. Therefore, it is difficult to reduce the electrode potential in order to increase the energy density.

[0007] On the other hand, regarding the capacity per unit weight, the theoretical capacity of titanium dioxide (anatase structure) is about 165 mAh / g, and that of Li4Ti5O 12The theoretical capacity of such spinel-type lithium-titanium composite oxide is also about 180 mAh / g. On the other hand, the theoretical capacity of general graphite-based electrode materials is above 385 mAh / g. As such, the capacity density of titanium oxide is significantly lower than that of carbon-based negative electrodes. This is because: in the crystal structure of titanium oxide, there are few sites for embedding lithium, and lithium is easily stabilized in the structure, so the actual capacity is reduced.

[0008] In view of the above situation, new electrode materials containing Ti and Nb have been studied. It is expected that niobium titanium oxide has a high charge and discharge capacity. For example, an oxide represented by TiNb2O7 has a high theoretical capacity of more than 380 mAh / g. However, niobium titanium oxide has low electronic conductivity, so the output performance is not excellent. Summary of the invention

[0009] The problem to be solved by the present invention is to provide an active material and an electrode for a secondary battery that can achieve high output performance and can show excellent life performance, a secondary battery and a battery pack that can achieve high output performance and can show excellent life performance, and a vehicle equipped with the battery pack.

[0010] According to an embodiment, an active material is provided, which includes a secondary particle, wherein the secondary particle includes a plurality of primary particles containing niobium oxide. The secondary particle includes adjacent portions where the primary particles are adjacent to each other, and a constricted portion where the primary particles are connected to each other. The sum of the total perimeter L of the primary particles and the perimeter L of the primary particles excluding the constricted portion is cl Satisfy 0.1<(LL cl ) / L≤0.6.

[0011] According to other embodiments, an electrode is provided, which includes the above-mentioned active material.

[0012] According to another embodiment, a secondary battery is provided, which includes a positive electrode, a negative electrode including a negative electrode active material, and an electrolyte. The negative electrode active material includes secondary particles, and the secondary particles include a plurality of primary particles containing niobium oxide. The secondary particles include a first adjacent portion where the primary particles are adjacent to each other, and a second adjacent portion where the primary particles are in contact with each other via an interface. The total perimeter L of the primary particles and the sum of the perimeters L of the primary particles excluding the second adjacent portion are equal to the sum L of the perimeters L of the primary particles. cl Satisfy 0.1≤(LL cl ) / L≤0.6.

[0013] According to another embodiment, there is provided a battery pack including the above-mentioned secondary battery.

[0014] According to another embodiment, a vehicle is provided, which is equipped with the above-mentioned battery pack.

[0015] According to the active material having the above-described configuration, it is possible to provide a secondary battery and a battery pack that have high output performance and can exhibit excellent life performance, and a vehicle including the battery pack. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is a cross-sectional view schematically showing secondary particles included in an example of the active material according to the embodiment.

[0017] Figure 2 This is a cross-sectional view schematically showing an example of a conventional active material secondary particle.

[0018] Figure 3 This is a scanning electron microscope image of a cross section of an example of an electrode including the active material according to the embodiment.

[0019] Figure 4 Yes Figure 3 The electron microscope image shown in FIG. 1 is a processed image obtained by binarizing and performing an erosion process.

[0020] Figure 5 Yes Figure 3 The electron microscope image shown in is binarized and closed.

[0021] Figure 6 This is a cross-sectional view schematically showing an example of a secondary battery according to an embodiment.

[0022] Figure 7 Yes Figure 6 A cross-sectional view of a secondary battery shown in FIG. 1 which is an enlarged view of a portion A of the secondary battery.

[0023] Figure 8 It is a partially cutaway perspective view schematically showing another example of the secondary battery according to the embodiment.

[0024] Fig. 9 Yes Figure 8 A cross-sectional view showing an enlarged portion B of the secondary battery shown in FIG.

[0025] Fig.10 It is a perspective view schematically showing an example of a battery pack according to an embodiment.

[0026] Fig.11 It is an exploded perspective view schematically showing an example of a battery pack according to an embodiment.

[0027] Fig.12 Yes means Fig.11 A block diagram of an example of a circuit of a battery pack is shown in FIG.

[0028] Fig.13This is a partial perspective view schematically showing an example of a vehicle according to the embodiment.

[0029] Fig.14 This is a diagram schematically showing an example of a control system related to an electrical system in a vehicle according to an embodiment.

[0030] (Explanation of symbols)

[0031] 1…electrode group, 2…outer packaging member, 3…negative electrode, 3a…negative electrode current collector, 3b…containing negative electrode active material layer, 3c…negative electrode collector ear, 4…separator, 5…positive electrode, 5a…positive electrode current collector, 5b…containing positive electrode active material layer, 6…negative electrode terminal, 7…positive electrode terminal, 11…primary particle, 12…secondary particle, 13…neck portion, 14…isolated particle, 15…periphery, 16…boundary, 21…busbar, 22… positive electrode side lead, 23 ... negative electrode side lead, 24 ... adhesive tape, 31 ... storage container, 32 ... cover, 33 ... protective sheet, 34 ... printed circuit wiring board, 35 ... wiring, 40 ... vehicle body, 41 ... vehicle power supply, 42 ... electric control device, 43 ... external terminal, 44 ... inverter, 45 ... drive motor, 100 ... secondary battery, 200 ... battery pack, 200a ... battery pack, 200b ... battery pack, 20 0c... battery pack, 300... battery pack, 300a... battery pack, 300b... battery pack, 300c... battery pack, 301a... battery pack monitoring device, 301b... battery pack monitoring device, 301c... battery pack monitoring device, 342... positive electrode side connector, 343... negative electrode side connector, 345... thermistor, 346... protection circuit, 342a... wiring, 343a... wiring, 350... external terminal for power supply , 352…positive side terminal, 353…negative side terminal, 348a…positive side wiring, 348b…negative side wiring, 400…vehicle, 411…battery management device, 412…communication bus, 413…positive terminal, 414…negative terminal, 415…switching device, 416…current detection unit, 417…negative input terminal, 418…positive input terminal, L1…connecting line, L2…connecting line, W…driving wheel. DETAILED DESCRIPTION

[0032] The present inventors have found through a hybrid pulse power characteristic (HPPC) test that the particle size of the active material has a great influence on the overvoltage at the solid-liquid interface, which accounts for most of the battery resistance, and the lithium (Li) concentration polarization inside the active material in a battery using niobium titanium oxide. Even when normality is observed in the particle size distribution of niobium titanium oxide particles, the resistance increase caused by the active material with a large particle size becomes significant. In particular, when the particle size distribution becomes wide, including coarse particles, the resistance increase caused by these coarse particles becomes more significant.

[0033] Hereinafter, the embodiments are described with reference to the accompanying drawings. It should be noted that the same symbols are used to mark the common components in the embodiments, and repeated descriptions are omitted. In addition, each figure is a schematic diagram for promoting the description and understanding of the embodiments, and its shape, size, proportion, etc. are different from the actual device, but they can be appropriately designed and changed with reference to the following description and known technologies.

[0034] (First embodiment)

[0035] According to a first embodiment, an active material is provided. The active material includes secondary particles containing niobium oxide. The secondary particles include a plurality of primary particles. The secondary particles include adjacent portions where primary particles are adjacent to each other and constricted portions where primary particles are connected to each other. The sum L of the total perimeter L of the primary particles and the perimeter L of the primary particles excluding the constricted portions is cl Satisfy 0.1<(LL cl ) / L≤0.6.

[0036] The constricted portion in the active material corresponds to a portion of the grain boundary between primary particles having higher Li diffusivity than the bulk. The active material can exhibit high Li diffusivity by having the constricted portion.

[0037] Figure 1 , a cross-sectional view schematically showing a secondary particle included in an example of the active material is shown. The illustrated secondary particle 12 includes a plurality of primary particles 11, and a portion of the primary particles 11 are joined to form a constriction 13. The presence of the constriction 13 maintains the Li conductivity and electron conductivity between the primary particles 11. Since the primary particles 11 are active material particles containing niobium oxide, they expand and contract as the electrode containing the active material is charged and discharged. As a result, although the constriction 13 is cracked, the primary particles 11 constituting the constriction 13 are not independent of each other.

[0038] The necking ratio N, which indicates the degree of necking caused by the primary particle 11 in the active material, is calculated by dividing the total perimeter L of the primary particle 11 by the sum of the perimeter L of the primary particle 11 excluding the necking portion 13. cl The relationship (LL cl ) / L to represent (that is, N = (LL cl ) / L). The details will be described later, but it shows the relationship between the necking ratio N (LL cl ) / L is obtained for an observation field containing 100 or more primary particles 11. The neck structure of the primary particle 11 in the secondary particle 12 satisfies 0.1<(LL cl) / L≤0.6 (0.1<N≤0.6), the Li conductivity is not easily impaired. In addition, for an electrode containing such an active material, the overvoltage during charge and discharge at a high rate is also low. The preferred (LL cl ) / L is in the range of 0.2 to 0.6, more preferably in the range of 0.4 to 0.5.

[0039] As a previous attempt to increase the electrode capacity, reducing the particle size and increasing the electrode density can be cited. In the case of increasing the density of the electrode in a state with a small particle size, the result of the expansion-contraction generated by charge and discharge is sometimes that the primary particles are compacted. If the fine primary particles in the electrode are compacted, isolated particles are easily generated in the center of the secondary particles. Since the Li conduction and electronic conduction between the isolated particles and other primary particles around them are low, the input and output performance is impaired, and the energy density is substantially reduced.

[0040] An example is shown in Figure 2 Although the secondary particle 12 shown in the figure includes a plurality of primary particles 11, it does not have constrictions between the primary particles 11. In addition, the center of the secondary particle 12 includes a primary particle isolated from other primary particles 11, that is, an isolated particle 14. A gap is generated between the isolated particle 14 and other primary particles 11 around it, and the resistance between the isolated particle 14 and the primary particle 11 is large.

[0041] As niobium-containing oxides, for example, niobium-titanium composite oxides can be cited. As an example of niobium-titanium composite oxides, Nb2TiO7 can be cited. The niobium-containing oxides are not limited thereto, but preferably at least a portion thereof has a symmetry of space group C2 / m and a crystal structure having atomic coordinates described in Non-Patent Document 1 (M. Gasperin, Journal of Solid State Chemistry 53, pp144-147 (1984)).

[0042] Niobium-containing oxides mainly show a monoclinic crystal structure. For example, when the crystal structure of monoclinic Nb2TiO7 is embedded with lithium ions, the metal ions constituting the skeleton of the crystal structure are reduced to trivalent, thereby maintaining the electrical neutrality of the crystal. In niobium titanium oxide, not only are Ti ions reduced from tetravalent to trivalent, but Nb ions are also reduced from pentavalent to trivalent. Therefore, the number of reduction valences per unit weight of the active material is large. Therefore, even if many lithium ions are embedded, the electrical neutrality of the crystal can be maintained. Therefore, compared with compounds such as titanium oxide containing only tetravalent cations, the energy density is high. In addition, niobium-containing oxides have a 1.5V (relative to Li / Li +) of lithium insertion potential. Therefore, an electrode containing niobium oxide as an active material can realize a battery that can perform stable repeated rapid charge and discharge.

[0043] The niobium-containing oxide may be niobium titanium oxide. For example, the niobium titanium oxide may include Nb2TiO7, Nb2Ti2O9, Nb 10 TiO 29 , Nb 14 TiO 37 and Nb 24 TiO 62 At least one crystalline phase in the group consisting of. Niobium titanium oxide may also be a substituted niobium titanium oxide in which at least a portion of Nb and / or Ti is substituted by a heterogeneous element. Examples of substitution elements are Na, K, Ca, Co, Ni, Si, P, V, Cr, Mo, Ta, Zr, Mn, Fe, Mg, B, Pb and Al. The substituted niobium titanium oxide may contain one substitution element or more than two substitution elements. The active material particles may contain one niobium titanium oxide or multiple niobium titanium oxides. Niobium titanium oxide preferably contains monoclinic niobium titanium oxide Nb2TiO7. In this case, as described above, an electrode with excellent capacity and rate performance can be obtained.

[0044] Examples of monoclinic niobium titanium oxide include Li x Ti 1-y M1 y Nb 2-z M2 z O 7+δ The compound represented by wherein M1 is at least one selected from the group consisting of Zr, Si, and Sn. M2 is at least one selected from the group consisting of V, Ta, and Bi. Each subscript in the composition formula is 0≤x≤5, 0≤y<1, 0≤z<2, -0.3≤δ≤0.3.

[0045] Other examples of monoclinic niobium titanium oxide include Ti 1-y M3 y+z Nb 2-z O 7-δ The compound represented by wherein M3 is at least one selected from Mg, Fe, Ni, Co, W, Ta, and Mo. Each subscript in the composition formula is 0≤y<1, 0≤z<2, -0.3≤δ≤0.3.

[0046] The active material may be only particles containing niobium oxide, or may contain active materials other than particles containing niobium oxide. The content of particles containing niobium oxide in the active material is preferably in the range of 75 wt % or more and 100 wt % or less. The closer the content of particles containing niobium oxide in the active material is to 100 wt %, the more preferable it is.

[0047] Examples of the active material other than niobium oxide (second active material) include lithium titanate having a ramsdellite structure (e.g., Li 2+y Ti3O7, 0≤y≤3), lithium titanate with spinel structure (e.g., Li 4+x Ti5O 12 , 0≤x≤3), monoclinic titanium dioxide (TiO2(B)), anatase titanium dioxide, rutile titanium dioxide, alkali pyrolusite titanium composite oxide and orthorhombic titanium-containing composite oxide.

[0048] Examples of the orthogonal titanium-containing composite oxide include Li 2+a M I 2-b Ti 6-c M II d O 14+σ The compound represented by I It is at least one selected from the group consisting of Sr, Ba, Ca, Mg, Na, Cs, Rb and K. M II At least one selected from the group consisting of Zr, Sn, V, Nb, Ta, Mo, W, Y, Fe, Co, Cr, Mn, Ni, and Al. The subscripts in the composition formula are 0≤a≤6, 0≤b<2, 0≤c<6, 0≤d<6, -0.5≤σ≤0.5. Specific examples of orthogonal titanium-containing composite oxides include Li 2+a Na2Ti6O 14 (0≤a≤6).

[0049] The average particle size of the primary particles containing niobium oxide is preferably in the range of 0.5 μm or more and 3 μm or less, and more preferably in the range of 0.5 μm or more and 2 μm or less. By setting the average particle size to be above 0.5 μm, the electrode density is increased, thereby making it possible to improve the contact between the active material particles in the electrode and the contact between the active material particles and the conductive agent, thereby improving the life performance. In addition, the reaction between the particles containing niobium oxide and the electrolyte can be suppressed, thereby improving the rapid charge and discharge performance. In addition, by setting the average particle size to be below 3 μm, the Li ion diffusion distance in the solid can be moderated to improve the rapid charge and discharge performance. The method for determining the average particle size is described below.

[0050] The crystallite size of the particles containing niobium oxide is, for example, in the range of 10 nm to 300 nm, preferably in the range of 50 nm to 200 nm, and more preferably in the range of 80 nm to 120 nm. If the crystallite size is within this range, Li ion conduction in the crystal is smoothly performed, thereby improving the charge and discharge efficiency and rate performance.

[0051] <Manufacturing method>

[0052] The active material can be produced by the following method.

[0053] First, the starting materials are mixed. As an example of niobium-containing oxides, oxides or salts containing Li, Ti, and Nb are used as starting materials for niobium titanium oxide. The salt used as the starting material is preferably a salt that decomposes at a relatively low temperature to produce an oxide, such as carbonates and nitrates. In addition, the particle size of these starting materials is preferably in the range of 0.1 μm to 10 μm, and more preferably in the range of 0.1 μm to 5 μm. This is because: if it is less than 0.1 μm, it is easy to fly in the atmosphere during mixing, which is easy to cause composition deviation, and if it is greater than 10 μm, unreacted products are produced.

[0054] In addition to the above starting materials containing the constituent elements of the oxide, a material containing at least S is further mixed in order to prepare a flux. As the material containing S that can be used in the flux, for example, sulfates such as sodium sulfate can be used. In addition to the material containing S, a material containing P or a material containing K can also be used in the flux.

[0055] When the starting raw materials are mixed, the Nb source and the Ti source are mixed in a molar ratio such that the target composition is obtained. The materials used to make the flux are mixed in an amount such that the molar ratio of S, P, and K to Nb is 1 or less. The mixed raw materials are subjected to temporary calcination for 2 to 5 hours at a temperature in the range of 500°C to 1000°C. The powder after the temporary calcination is crushed in a ball mill for 1 hour and then subjected to formal calcination. The formal calcination is carried out in two or more calcinations at a temperature of 1000°C to 1450°C for a total of 10 to 40 hours.

[0056] After the formal firing, the obtained powder is provided to the pulverizing process. In the pulverizing process, first, a roller compressor or a hammer mill is used for strong pulverization. After that, a wet ball mill is used for pulverization for 1 to 5 hours. At this time, since the crystallinity of the product decreases, the crystallite diameter becomes smaller. Next, a reheat treatment is performed at the same temperature as the temperature during the formal firing. The reheat treatment is, for example, a heat treatment for 0.5 to 5 hours. The reheat treatment is preferably performed using an electric furnace that has been preheated to the target temperature. In addition, after the reheat treatment, it is preferred to cool the powder quickly. In this way, the particle growth during the heating and cooling of the electric furnace can be suppressed. The cooling after the reheat treatment is preferably carried out under the condition that the temperature of the sintered powder becomes below 100°C within 1 hour from the temperature during the sintering.

[0057] In this way, after implementing a pulverization process including strong pulverization, for example, by performing a reheat treatment at the same temperature as the formal sintering, the reduction in crystallinity caused by the pulverization is restored, and particles with a large crystallite diameter can be obtained. The manufacturing method including the strong pulverization process and the reheat treatment process can manufacture active material particles with high crystallinity and a small average primary particle size.

[0058] Furthermore, by using a flux containing at least S, an active material in which the necking ratio N within the above-mentioned range is observed can be obtained.

[0059] The material used in the flux also affects the growth of particles. When using a substance such as a sulfate containing S as a flux, since it has a relatively low melting point and is easy to volatilize, it is easy to obtain the effect of the flux even at a low temperature. In addition, on the other hand, since it is not easy to form a stable phase similar to the parent phase, it is not easy to generate an impurity phase even if the S flux is present in a high concentration. Accordingly, since the solubility of the solute is low, the effect of promoting particle growth is not so high, and the effect of the addition of the flux on the secondary particle size is low. Therefore, for the S flux, an effect such as promoting the necking of the particles can be expected.

[0060] When P is used as a raw material of a flux, raw materials such as phosphates have a high melting point. Therefore, in order to obtain sufficient vapor pressure near the surface of the active material particles to function as a flux, it becomes necessary to sinter at a relatively high temperature. Regarding the solubility of the active material to be the solute, since there are energetically stable titanium or niobium phosphates, it is easy to dissolve the raw material of the negative electrode active material to be the solute. Therefore, at a high temperature where the P flux is fully melted, the effect of promoting particle growth is high, and there is an effect of increasing the primary particle size. On the other hand, if the concentration of the P flux is high, these phosphates are easily generated as impurities, so excessive addition will cause the purity of the active material to decrease.

[0061] Regarding the flux containing K, if it is a compound with a low melting point such as KCl or KNO3, the same effect as the above-mentioned S can be obtained. The melting points of these substances tend to be lower than those of sulfates, so the effect of the flux can be expected even at lower temperatures. Furthermore, since there are many stable phases in the phase diagram of K2O-Nb2O5, high solubility can be expected for the active material that becomes the solute. Therefore, the K flux shows the function of promoting particle growth like the P flux. It should be noted that in the case of the K flux, the K-containing substance can become an impurity like the P flux.

[0062] K and P impurities can form grain boundaries between microcrystals containing niobium oxide. In addition to the impurity elements, niobium can be contained in the grain boundaries as in the parent phase. A portion of such grain boundaries becomes a necking portion between primary particles. The concentration of impurity elements in the grain boundaries is preferably 20% or more higher than that in the parent phase. In other words, the purity of the parent phase becomes higher by the impurities staying at the grain boundaries, and the performance as an active material becomes better.

[0063] It should be noted that the niobium titanium oxide synthesized by the above method can also be intercalated with lithium ions by charging a battery. Alternatively, as described above, it can be synthesized as a lithium-containing oxide by using a lithium-containing compound such as lithium carbonate as a starting material.

[0064] Next, the necking ratio N (relationship (LL cl The measurement methods of ) / L) etc. are described below.

[0065] <Measurement of Neck Shrinkage Ratio N>

[0066] The quantitative evaluation of the necking between active materials can be performed by analyzing a scanning electron microscope (SEM) image of a cross section of an electrode including the active material.

[0067] The cross section of the electrode sample was cut out by Ar ion milling, and the cut cross section was observed using a SEM.

[0068] The magnification of the SEM image is preferably about 5000 times from the balance between the number of particles measured and the resolution. The total number of particles measured is set to ensure that more than 100 particles are obtained in order to improve the quantitative accuracy. In the case where it is difficult to observe 100 particles through one SEM image, multiple fields of view are combined to observe a total of more than 100 particles for analysis. The detection mode selects a method in which the periphery of the active material particles can be clearly observed, and the difference between the active material to be measured and other components becomes clear from the contrast.

[0069] The obtained SEM image can be converted to a binary image using analysis software such as ImageJ. First, the SEM image is converted into an 8-bit monochrome image, and then a threshold is set and converted into a binary image represented only by brightness 0 (black) and 255 (white). For setting the threshold, it is preferred to use a discriminant analysis method that can set a threshold that maximizes the separation degree. For the obtained binary image, corrosion treatment is performed in a state where the active material particles belong to a brightness of 255, and each area closed by the observed brightness 255 is shrunk by only 1 pixel. In this way, the connection and noise of adjacent particles can be eliminated and the boundaries of the particles can be made clear. The obtained image is subjected to particle analysis to measure the total number of particles n and the total circumference L of the primary particles. Furthermore, by assuming that all particles are perfect circles, the average particle size D can be calculated by D=L / nπ.

[0070] Next, the original image just after binary conversion is expanded so that each area closed by the observed brightness of 255 is expanded by only 1 pixel. After that, the erosion process is performed twice. Through this closing process, the tiny gaps between particles detected in the original binary image can be filled. After that, the particle analysis is performed in the same way as before, and the total number of particles and the sum of the perimeters of the primary particles excluding the necking part L are measured. cl .L cl It represents the total circumference obtained by removing the constricted part from the total circumference of the primary particle. This is an analysis method that utilizes the splitting of the constricted part of the active material particles due to the volume change caused by charging and discharging. For the simple gap formed only between the initially adjacent particles, which is different from the constriction, there is no change before and after the expansion treatment. On the other hand, for the constricted part, since the gap is filled by the closing treatment, it is not measured as the circumference in the image after the closing treatment. Therefore, LL cl Value (L minus L cl The value obtained by the closure process represents the reduced perimeter, which corresponds to the perimeter after the necking. Therefore, the ratio N of the necking area of ​​the particle is N = (LL cl ) / L.

[0071] The measurement using cross-sectional SEM is to measure the area cut by an arbitrary line of a part of the necking surface. Depending on the area cut, even if the necking surface is the same, the length becomes different depending on the cutting method. Therefore, in order to quantify the information corresponding to the total area of ​​only the necking area by analyzing the cross-sectional SEM image, a sufficient number of particles (more than 100) are analyzed.

[0072] An example of a cross-sectional SEM image and a processed image is shown in Figure 3 to Figure 5 middle. Figure 3 is an example of a SEM image of an electrode cross section. Figure 4 Yes Figure 3 The SEM image of is converted into a binary image and eroded without dilation. Figure 5 Yes Figure 3 The SEM image of the image was converted to binary and then subjected to dilation and two corrosion processes (closing process). Figure 4 In the figure, the boundaries 16 observed in some places between particles are Figure 5 The boundary 16 that disappears due to the closing process corresponds to the necking portion in the active material before charge and discharge. Figure 4 The total perimeter L of the primary particles is calculated by taking the total length of the periphery 15 of the active material particles in the primary particles. Figure 5 The area corresponding to the necking portion is excluding the outer circumference 15, and the Figure 5 The total length of the outer circumference 15 in the figure is calculated to obtain the total circumference L excluding the necking part. cl .

[0073] <Confirmation of the crystal structure and crystallite diameter of the active substance>

[0074] The crystal structure and crystallite diameter of the active material can be confirmed by, for example, combining powder X-ray diffraction measurement (X-Ray Diffraction: XRD) with analysis by the Rietveld method.

[0075] The powder X-ray diffraction measurement of the active material can be performed, for example, as follows.

[0076] First, the active material is crushed as needed to prepare a sample with an average particle size of less than about 5μm. The average particle size can be obtained by laser diffraction. The obtained sample is filled into a retainer portion with a depth of 0.2mm formed on a glass sample plate. Next, another glass plate is pressed from the outside to flatten the surface of the filled sample. Be careful not to fill too much or too little sample to avoid cracks, voids, bumps, etc. in the filled sample. In addition, be careful to press the glass plate with sufficient pressure. Next, the glass plate filled with the sample is placed in a powder X-ray diffraction device, and the XRD pattern is obtained using Cu-Kα rays.

[0077] It should be noted that, when the sample has a high orientation, the position of the peak may deviate or the peak intensity ratio may change depending on the filling method of the sample. Such a sample with a significantly high orientation is measured using a capillary. Specifically, the sample is inserted into a capillary and the capillary is placed on a rotating sample stand for measurement. By such a measurement method, the orientation can be relaxed. For the capillary, a capillary made of Lindemann glass is used.

[0078] The active material contained in the battery as an electrode material can be measured as follows. First, it is set to a state where lithium ions are completely separated from the active material (such as niobium titanium oxide) in the electrode material. For example, when the active material is used for the negative electrode, the battery is put into a fully discharged state. In this way, the crystalline state of the active material can be observed. Sometimes there are residual lithium ions even in the discharged state. Due to the influence of the lithium ions remaining in the electrode, impurity phases such as lithium carbonate and lithium fluoride are sometimes mixed into the powder X-ray diffraction measurement results. The mixing of impurity phases can be prevented, for example, by setting the measurement atmosphere to an inert gas atmosphere or washing the electrode surface. Even if there are impurity phases, these phases can be ignored and analyzed.

[0079] Next, the battery is disassembled in a glove box filled with argon, and the electrode is taken out. The taken-out electrode is washed with a suitable solvent. For example, ethyl methyl carbonate or the like can be used. The washed electrode is cut into an area substantially the same as the area of ​​the holder of the powder X-ray diffraction apparatus as a measurement sample.

[0080] The cut sample (electrode) is directly attached to the glass holder for measurement. At this time, the position of the peak originating from the electrode substrate such as metal foil is measured in advance. In addition, the peaks of other components such as conductive agents and binders are also measured in advance. In the case where the peak of the substrate overlaps with the peak of the active material, it is preferred to peel off the layer containing the active material (for example, the active material-containing layer described later) from the substrate for measurement. This is to separate the overlapping peaks when the peak intensity is quantitatively measured. For example, by irradiating the electrode substrate with ultrasound in a solvent, the active material layer can be peeled off. The XRD pattern obtained at this time must be suitable for Rietveld analysis. In order to collect Rietveld data, the step size is made 1 / 3 to 1 / 5 of the minimum half-value width of the diffraction peak, and the measurement time and / or X-ray intensity are appropriately adjusted in such a way that the intensity at the peak position of the most intense reflection becomes 5000 to 10000 counts.

[0081] The obtained XRD pattern is analyzed by the Rietveld method. In the Rietveld method, the diffraction pattern is calculated by the crystal structure model estimated in advance. By carrying out full fitting of the calculated value and the measured value, the parameters (lattice constant, atomic coordinates, occupancy rate, etc.) related to the crystal structure can be accurately analyzed. Thus, the characteristics of the crystal structure of the synthesized oxide can be investigated. In addition, the occupancy rate in each site of the constituent element can be investigated.

[0082] In order to find the crystallite diameter (crystal size), the diffraction line with the strongest diffraction intensity is selected. For example, for monoclinic niobium titanium oxide, the peak of the (110) plane is measured. The crystallite size can be calculated from the half-value width of the obtained peak. Here, the crystallite size is calculated by the Scherrer formula shown in the following formula 1.

[0083] [Mathematical formula 1]

[0084]

[0085] Here, K = 0.9, λ = 0.15406 nm, β e : Half-value width of diffraction peak, β o : Correction value of half-value width (0.07°).

[0086] <Method for Confirming the Composition of Active Substances>

[0087] The composition of the active material can be analyzed, for example, using inductively coupled plasma (ICP) emission spectrometry. At this time, the existence ratio (molar ratio) of each element depends on the sensitivity of the analytical device used. Therefore, sometimes the measured molar ratio deviates from the actual molar ratio by a value corresponding to the error of the measuring device. However, even if the value deviates within the error range of the analytical device, the performance of the active material of the embodiment can be fully exerted.

[0088] The composition of the active material incorporated in the battery is measured by ICP emission spectroscopy, specifically, by the following procedure.

[0089] First, the electrode containing the active material to be measured is taken out from the secondary battery and washed by the steps described in the section of powder X-ray diffraction. The portion containing the electrode active material, such as the active material layer, is peeled off from the washed electrode. For example, the portion containing the electrode active material can be peeled off by irradiating with ultrasonic waves. As a specific example, for example, an electrode is placed in ethyl methyl carbonate placed in a glass beaker and vibrated in an ultrasonic washing machine, thereby peeling off the active material layer containing the electrode active material from the electrode collector.

[0090] Next, the stripped portion is heated in the atmosphere for a short time (for example, at 500°C for about 1 hour) to burn off useless components such as the binder component and the conductive agent (for example, carbon material) described later. By dissolving the residue with an acid, a liquid sample containing an active material can be prepared. At this time, hydrochloric acid, nitric acid, sulfuric acid, hydrofluoric acid, etc. can be used as an acid. By subjecting the liquid sample to ICP analysis, the composition of the active material can be known.

[0091] <Method for Confirming Impurity Elements>

[0092] The concentration of impurity elements in the matrix phase containing niobium oxide and in the grain boundaries between crystallites can be measured as follows.

[0093] The necking position at the particle interface of the active material is observed by a transmission electron microscope (TEM). The composition of the grain boundary can be quantified by energy dispersive X-ray spectroscopy (EDX) and compared with the composition of the parent phase. In this way, the impurity elements that exist unevenly in the grain boundary can be quantified.

[0094] The active material of the first embodiment includes secondary particles containing niobium oxide. The secondary particles include a plurality of primary particles, including adjacent portions where the primary particles are adjacent to each other and constricted portions where the primary particles are connected to each other. The sum of the total perimeter L of the primary particles and the perimeter L of the primary particles excluding the constricted portions is cl Satisfy 0.1<(LL cl ) / L≤0.6. The active material can provide a secondary battery with high output performance and excellent life performance.

[0095] (Second embodiment)

[0096] According to a second embodiment, an electrode is provided.

[0097] The electrode of the second embodiment includes the active material of the first embodiment. The electrode may be a battery electrode including the active material of the first embodiment as a battery active material. The electrode as a battery electrode may be, for example, a negative electrode including the active material of the first embodiment as a negative electrode active material.

[0098] The electrode may include a current collector and an active material-containing layer. The active material-containing layer may be formed on one side or both sides of the current collector. The active material-containing layer may include an active material and optionally a conductive agent and a binder.

[0099] Conductive agents are formulated to improve current collection performance and suppress the contact resistance between the active material and the current collector. Examples of conductive agents include carbon blacks such as vapor grown carbon fiber (VGCF), acetylene black, graphite, carbon nanotubes, and carbon nanofibers. One of them can be used as a conductive agent, or two or more can be combined and used as a conductive agent. Alternatively, instead of using a conductive agent, the surface of the active material particles can also be coated with carbon or an electronically conductive inorganic material.

[0100] The binder is used to fill the gaps between the dispersed active materials and to bind the active materials to the current collector. Examples of binders include polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVdF), fluorine rubber, styrene-butadiene rubber, polyacrylic acid compounds, imide compounds, carboxymethyl cellulose (CMC) and salts of CMC. One of them can be used as a binder, or two or more can be combined and used as a binder.

[0101] The proportion of active material, conductive agent and binder in the active material layer can be appropriately changed according to the purpose of the electrode. For example, when the electrode is used as the negative electrode of a secondary battery, it is preferred that the active material (negative electrode active material), conductive agent and binder are respectively matched in a ratio of 68% by mass or more and 96% by mass or less, 2% by mass or more and 30% by mass or less, and 2% by mass or more and 30% by mass or less. By setting the amount of conductive agent to more than 2% by mass, the current collection performance of the active material layer can be improved. In addition, by setting the amount of binder to more than 2% by mass, the binding property of the active material layer and the collector becomes sufficient, and excellent cycle performance can be expected. On the other hand, the conductive agent and binder are respectively set to less than 30% by mass, which is preferred in terms of seeking high capacity.

[0102] The current collector may use a material that is electrochemically stable at a potential at which lithium (Li) is embedded and de-embedded in the active material. For example, when the active material is used as the negative electrode active material, the current collector is preferably made of copper, nickel, stainless steel or aluminum, or an aluminum alloy containing one or more elements selected from Mg, Ti, Zn, Mn, Fe, Cu and Si. The thickness of the current collector is preferably 5 μm or more and 20 μm or less. A current collector having such a thickness can achieve a balance between the strength and lightness of the electrode.

[0103] Furthermore, the current collector may include a portion on the surface of which the negative electrode active material-containing layer is not formed. This portion may function as a negative electrode collector tab.

[0104] The electrode can be made, for example, by the following method. First, an active material, a conductive agent, and a binder are suspended in a solvent to prepare a slurry. The slurry is applied to one or both sides of a current collector. Next, the applied slurry is dried to obtain a laminate containing an active material layer and a current collector. Thereafter, the laminate is pressed. In this way, an electrode is made.

[0105] Alternatively, the electrode can also be made by the following method. First, the active material, the conductive agent and the binder are mixed to obtain a mixture. Then, the mixture is formed into particles. Then, the particles are arranged on a current collector to obtain an electrode.

[0106] The electrode of the second embodiment includes the active material of the first embodiment. Therefore, the electrode can provide a secondary battery having high output performance and excellent life performance.

[0107] (Third embodiment)

[0108] According to a third embodiment, a secondary battery is provided, which includes a positive electrode, a negative electrode containing a negative electrode active material, and an electrolyte. The negative electrode active material includes secondary particles, and the secondary particles include a plurality of primary particles containing niobium oxide. The secondary particles include a first adjacent portion where the primary particles are adjacent to each other and a second adjacent portion where the primary particles are in contact with each other via an interface. The total perimeter L of the primary particles and the sum L of the perimeters of the primary particles excluding the second adjacent portions are equal to the sum L of the perimeters of the primary particles. cl Satisfy 0.1≤(LL cl ) / L≤0.6.

[0109] The secondary battery may be a battery including the electrode of the second embodiment as a negative electrode. That is, the secondary battery of the third embodiment may be a battery including, as a negative electrode, an electrode containing the active material of the first embodiment as a battery active material. However, as described in the first embodiment, the necking portion of the active material cracks due to the volume change caused by charging and discharging. That is, the second adjacent portion corresponds to the portion where the necking cracks. The first adjacent portion corresponds to the portion where the primary particles are adjacent to each other since before the necking cracks. The above relationship (LL cl ) / L represents the ratio of the second adjacent portion, corresponding to the necking ratio N. (LL cl ) / L is determined as described above.

[0110] The secondary battery may further include a separator disposed between the positive electrode and the negative electrode. The negative electrode, the positive electrode and the separator may constitute an electrode group. The electrolyte may be retained in the electrode group.

[0111] In addition, the secondary battery may further include an outer packaging member that accommodates the electrode group and the electrolyte.

[0112] Furthermore, the secondary battery may further include a negative electrode terminal electrically connected to the negative electrode and a positive electrode terminal electrically connected to the positive electrode.

[0113] The secondary battery may be, for example, a lithium secondary battery. The secondary battery includes a non-aqueous electrolyte secondary battery containing a non-aqueous electrolyte.

[0114] Hereinafter, the negative electrode, positive electrode, electrolyte, separator, outer packaging member, negative electrode terminal, and positive electrode terminal will be described in detail.

[0115] 1) Negative electrode

[0116] The negative electrode may include a negative electrode current collector and a negative electrode active material-containing layer. The negative electrode current collector and the negative electrode active material-containing layer may be the current collector and the active material-containing layer that the electrode of the second embodiment may include, respectively. The negative electrode active material-containing layer contains the active material of the first embodiment as the negative electrode active material.

[0117] In the details of the negative electrode, the parts that overlap with the details described for the second embodiment are omitted.

[0118] The density of the negative electrode active material-containing layer (excluding the current collector) is preferably 1.8 g / cm 3 or more and 2.8 g / cm 3 or less. The negative electrode having the density of the negative electrode active material-containing layer within this range has excellent energy density and electrolyte retention. The density of the negative electrode active material-containing layer is more preferably 2.1 g / cm 3 or more and 2.6 g / cm 3 or less.

[0119] The negative electrode can be produced, for example, by the same method as the electrode of the second embodiment.

[0120] 2) Positive electrode

[0121] The positive electrode may include a positive electrode current collector and a positive electrode active material-containing layer. The positive electrode active material-containing layer may be formed on one or both surfaces of the positive electrode current collector. The positive electrode active material-containing layer may include a positive electrode active material and an optional conductive agent and binder.

[0122] As the positive electrode active material, for example, an oxide or a sulfide can be used. The positive electrode may contain one compound alone as the positive electrode active material, or may contain two or more compounds in combination. Examples of the oxide and sulfide include compounds capable of intercalating and deintercalating Li or Li ions.

[0123] As such a compound, for example, it includes manganese dioxide (MnO2), iron oxide, copper oxide, nickel oxide, lithium manganese composite oxide (for example, Li x Mn2O4 or Li x MnO2; 0 < x ≤ 1), lithium nickel composite oxide (for example, Li x NiO2; 0 < x ≤ 1), lithium cobalt composite oxide (for example, Li x CoO2; 0 < x ≤ 1), lithium nickel cobalt composite oxide (for example, Li x Ni 1-y Co yO2; 0 < x ≤ 1, 0 < y < 1), lithium manganese cobalt composite oxide (e.g., Li x Mn y Co 1-y O2; 0 < x ≤ 1, 0 < y < 1), lithium manganese nickel composite oxide with spinel structure (e.g., Li x Mn 2-y Ni y O4; 0 < x ≤ 1, 0 < y < 2), lithium phosphorus oxide with olivine structure (e.g., Li x FePO4; 0 < x ≤ 1, Li x Fe 1-y Mn y PO4; 0 < x ≤ 1, 0 < y ≤ 1, Li x CoPO4; 0 < x ≤ 1), iron sulfate (Fe2(SO4)3), vanadium oxide (e.g., V2O5) and lithium nickel cobalt manganese composite oxide (Li x Ni 1-y-z Co y Mn z O2; 0 < x ≤ 1, 0 < y < 1, 0 < z < 1, y + z < 1).

[0124] Among the above, examples of more preferred compounds as the positive electrode active material include lithium manganese composite oxide with spinel structure (e.g., Li x Mn2O4; 0 < x ≤ 1), lithium nickel composite oxide (e.g., Li x NiO2; 0 < x ≤ 1), lithium cobalt composite oxide (e.g., Li x CoO2; 0 < x ≤ 1), lithium nickel cobalt composite oxide (e.g., Li x Ni 1-y Co y O2; 0 < x ≤ 1, 0 < y < 1), lithium manganese nickel composite oxide with spinel structure (e.g., Li x Mn 2-y Ni y O4; 0 < x ≤ 1, 0 < y < 2), lithium manganese cobalt composite oxide (e.g., Li x Mn y Co 1-y O2; 0 < x ≤ 1, 0 < y < 1), lithium iron phosphate (e.g., Li x FePO4; 0 < x ≤ 1) and lithium nickel cobalt manganese composite oxide (Li x Ni 1-y-z Co y Mn z O2; 0 < x ≤ 1, 0 < y < 1, 0 < z < 1, y + z < 1). If these compounds are used as the positive electrode active material, the positive electrode potential can be increased.

[0125] When using room temperature molten salt as the electrolyte of the battery, it is preferable to use a battery containing lithium iron phosphate, Li x Positive electrode active materials of VPO4F (0≤x≤1), lithium manganese composite oxide, lithium nickel composite oxide, lithium nickel cobalt composite oxide, or mixtures thereof. These compounds have low reactivity with room temperature molten salts, and thus can improve cycle life. Details of room temperature molten salts are described below.

[0126] The primary particle size of the positive electrode active material is preferably 100 nm or more and 1 μm or less. Positive electrode active materials with a primary particle size of 100 nm or more are easy to handle in industrial production. Positive electrode active materials with a primary particle size of 1 μm or less can smoothly perform solid diffusion of lithium ions.

[0127] The specific surface area of ​​the positive electrode active material is preferably 0.1 m 2 / g or more and 10m 2 / g or less. With 0.1m 2 / g or more of the positive electrode active material can fully secure the insertion and extraction sites of Li ions. 2 A positive electrode active material having a specific surface area of ​​100 Å / g or less is easy to handle in industrial production and can ensure good charge and discharge cycle performance.

[0128] The binder is used to fill the gaps between the dispersed positive electrode active materials and to bind the positive electrode active materials to the positive electrode collector. Examples of binders include polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVdF), fluorine rubber, polyacrylic acid compounds, imide compounds, carboxymethyl cellulose (CMC) and salts of CMC. One of them can be used as a binder, or two or more can be combined and used as a binder.

[0129] The conductive agent is formulated to improve the current collection performance and suppress the contact resistance between the positive electrode active material and the positive electrode collector. Examples of conductive agents include carbon black such as vapor grown carbon fiber (VGCF), acetylene black, and carbonaceous materials such as graphite. One of them can be used as a conductive agent, or two or more can be combined and used as a conductive agent. In addition, the conductive agent can be omitted.

[0130] In the positive electrode active material-containing layer, the positive electrode active material and the binder are preferably blended in a ratio of 80 mass % to 98 mass % and 2 mass % to 20 mass %, respectively.

[0131] By setting the amount of the binder to 2% by mass or more, sufficient electrode strength can be obtained. In addition, the binder can function as an insulator. Therefore, if the amount of the binder is set to 20% by mass or less, the amount of the insulator contained in the electrode is reduced, so the internal resistance can be reduced.

[0132] When a conductive agent is added, the positive electrode active material, the binder and the conductive agent are preferably blended in proportions of 77 mass % to 95 mass %, 2 mass % to 20 mass %, and 3 mass % to 15 mass %, respectively.

[0133] By setting the amount of the conductive agent to 3% by mass or more, the above-mentioned effect can be exerted. In addition, by setting the amount of the conductive agent to 15% by mass or less, the proportion of the conductive agent in contact with the electrolyte can be reduced. If this proportion is low, then under high temperature storage, the decomposition of the electrolyte can be reduced.

[0134] The positive electrode current collector is preferably an aluminum foil or an aluminum alloy foil containing one or more elements selected from Mg, Ti, Zn, Ni, Cr, Mn, Fe, Cu, and Si.

[0135] The thickness of the aluminum foil or aluminum alloy foil is preferably 5 μm or more and 20 μm or less, more preferably 15 μm or less. The purity of the aluminum foil is preferably 99% by mass or more. The content of transition metals such as iron, copper, nickel and chromium contained in the aluminum foil or aluminum alloy foil is preferably 1% by mass or less.

[0136] Furthermore, the positive electrode current collector may include a portion on the surface of which the positive electrode active material-containing layer is not formed. This portion may function as a positive electrode current collector tab.

[0137] The positive electrode can be produced, for example, by using a positive electrode active material in the same method as that of the electrode of the second embodiment.

[0138] 3) Electrolytes

[0139] As the electrolyte, for example, a liquid nonaqueous electrolyte or a gel nonaqueous electrolyte can be used. The liquid nonaqueous electrolyte can be prepared by dissolving an electrolyte salt as a solute in an organic solvent. The concentration of the electrolyte salt is preferably 0.5 mol / L or more and 2.5 mol / L or less.

[0140] Examples of electrolyte salts include lithium salts such as lithium perchlorate (LiClO4), lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium hexafluoroarsenate (LiAsF6), lithium trifluoromethanesulfonate (LiCF3SO3) and bistrifluoromethanesulfonyl imide (LiN(CF3SO2)2) and mixtures thereof. The electrolyte salt is preferably a substance that is difficult to oxidize even at a high potential, and LiPF6 is most preferred.

[0141] Examples of the organic solvent include cyclic carbonates such as propylene carbonate (PC), ethylene carbonate (EC), and vinylene carbonate (VC); chain carbonates such as diethyl carbonate (DEC), dimethyl carbonate (DMC), and methyl ethyl carbonate (MEC); cyclic ethers such as tetrahydrofuran (THF), 2-methyltetrahydrofuran (2MeTHF), and dioxolane (DOX); chain ethers such as dimethoxyethane (DME) and diethoxyethane (DEE); γ-butyrolactone (GBL), acetonitrile (AN), and sulfolane (SL). These organic solvents may be used alone or as a mixed solvent.

[0142] The gel non-aqueous electrolyte is prepared by compounding a liquid non-aqueous electrolyte with a polymer material. Examples of the polymer material include polyvinylidene fluoride (PVdF), polyacrylonitrile (PAN), polyethylene oxide (PEO), or a mixture thereof.

[0143] Alternatively, as the nonaqueous electrolyte, besides a liquid nonaqueous electrolyte and a gel nonaqueous electrolyte, a room-temperature molten salt (ionic melt) containing lithium ions, a polymer solid electrolyte, an inorganic solid electrolyte, or the like may be used.

[0144] Normal temperature molten salt (ionic melt) refers to a compound that can exist as a liquid at room temperature (15°C or more and 25°C or less) in an organic salt formed by a combination of an organic cation and an anion. Normal temperature molten salts include normal temperature molten salts that exist as liquids in the form of monomers, normal temperature molten salts that become liquids by mixing with electrolyte salts, normal temperature molten salts that become liquids by dissolving in organic solvents, or mixtures thereof. Generally speaking, the melting point of normal temperature molten salts used in secondary batteries is below 25°C. In addition, organic cations generally have a quaternary ammonium skeleton.

[0145] A polymer solid electrolyte can be prepared by dissolving an electrolyte salt in a polymer material and solidifying it.

[0146] Inorganic solid electrolytes are solid materials with Li ion conductivity. Here, Li ion conductivity means that the electrolyte has a Li ion conductivity of 1×10 -6 S / cm or higher lithium ion conductivity. Examples of the inorganic solid electrolyte include oxide-based solid electrolytes and sulfide-based solid electrolytes. Specific examples of the inorganic solid electrolyte are as follows.

[0147] As the oxide-based solid electrolyte, it is preferred to use a NASICON (Sodium (Na) Super Ionic Conductor) type structure having a general formula of Li 1+x A lithium phosphate solid electrolyte represented by Mα2(PO4)3. Mα in the above general formula is, for example, one or more selected from the group consisting of titanium (Ti), germanium (Ge), strontium (Sr), zirconium (Zr), tin (Sn), aluminum (Al) and calcium (Ca). The subscript x is in the range of 0≤x≤2.

[0148] As specific examples of lithium phosphate solid electrolytes having a NASICON structure, Li 1+ x Al x Ti 2-x LATP compounds represented by (PO4)3 and 0.1≤x≤0.5; Li 1+x Al y Mβ 2-y (PO4)3, wherein Mβ is one or more selected from the group consisting of Ti, Ge, Sr, Zr, Sn, and Ca, and 0≤x≤1 and 0≤y≤1; and Li 1+ x Al x Ge 2-x A compound represented by (PO4)3 and 0≤x≤2; and Li 1+x Al x Zr 2-xCompounds represented by (PO4)3 and 0 ≤ x ≤ 2; with Li 1+x+y Al x Mγ 2-x Si y P 3-y O 12 represented, and Mγ is one or more selected from the group consisting of Ti and Ge, and 0 < x ≤ 2, 0 ≤ y < 3; with Li 1+2x Zr 1-x Ca x represented by (PO4)3 and 0 ≤ x < 1.

[0149] In addition, as the oxide-based solid electrolyte, in addition to the above lithium phosphate solid electrolyte, there can also be mentioned amorphous LIPON compounds represented by Li x PO y N z and 2.6 ≤ x ≤ 3.5, 1.9 ≤ y ≤ 3.8, and 0.1 ≤ z ≤ 1.3 (for example, Li 2.9 PO 3.3 N 0.46 ); garnet-type structured compounds represented by La 5+x A x La 3-x Mδ2O 12 and A is one or more selected from the group consisting of Ca, Sr, and Ba, and Mδ is one or more selected from the group consisting of Nb and Ta, and 0 ≤ x ≤ 0.5; compounds represented by Li3Mδ 2-x L2O 12 and Mδ is one or more selected from the group consisting of Nb and Ta, and L may contain Zr, and 0 ≤ x ≤ 0.5; compounds represented by Li 7-3x Al x La3Zr3O 12 and 0 ≤ x ≤ 0.5; compounds represented by Li 5+x La3Mδ 2-x Zr x O 12 and Mδ is one or more selected from the group consisting of Nb and Ta, and 0 ≤ x ≤ 2, LLZ compounds (for example, Li7La3Zr2O 12 ); and compounds having a perovskite-type structure and represented by La 2 / 3-x Li x TiO3 and 0.3 ≤ x ≤ 0.7.

[0150] One or more of the above compounds can be used as the solid electrolyte. Two or more of the above solid electrolytes can also be used.

[0151] 4) Separator

[0152] The separator is formed of, for example, a porous film containing polyethylene (PE), polypropylene (PP), cellulose, or polyvinylidene fluoride (PVdF), or a synthetic resin nonwoven fabric. From the perspective of safety, a porous film formed of polyethylene or polypropylene is preferably used. This is because these porous films melt at a certain temperature and can cut off the current.

[0153] 5) Outer packaging components

[0154] As the outer packaging member, for example, a container made of a laminate film or a metal container can be used.

[0155] The thickness of the laminate film is, for example, 0.5 mm or less, or preferably 0.2 mm or less.

[0156] As the laminated film, a multilayer film including a plurality of resin layers and a metal layer sandwiched between the resin layers is used. The resin layer includes, for example, a polymer material such as polypropylene (PP), polyethylene (PE), nylon, and polyethylene terephthalate (PET). For the purpose of weight reduction, the metal layer is preferably made of aluminum foil or aluminum alloy foil. The laminated film can be formed into the shape of an outer packaging member by sealing using hot melt bonding.

[0157] The thickness of the wall of the metal container is, for example, 1 mm or less, more preferably 0.5 mm or less, and further preferably 0.2 mm or less.

[0158] The metal container is made of, for example, aluminum or an aluminum alloy. The aluminum alloy preferably contains elements such as magnesium, zinc, and silicon. When the aluminum alloy contains transition metals such as iron, copper, nickel, and chromium, the content thereof is preferably 100 mass ppm or less.

[0159] The shape of the outer packaging member is not particularly limited. The shape of the outer packaging member may be, for example, flat (thin), square, cylindrical, coin-shaped, or button-shaped. The outer packaging member may be appropriately selected according to the battery size or the purpose of the battery.

[0160] 6) Negative terminal

[0161] The negative terminal can be formed of a material that is electrochemically stable and conductive at the Li insertion and extraction potential of the above-mentioned negative electrode active material. Specifically, as the material of the negative terminal, copper, nickel, stainless steel or aluminum, or an aluminum alloy containing at least one element selected from the group consisting of Mg, Ti, Zn, Mn, Fe, Cu, and Si can be listed. As the material of the negative terminal, aluminum or an aluminum alloy is preferably used. In order to reduce the contact resistance with the negative electrode collector, the negative terminal is preferably made of the same material as the negative electrode collector.

[0162] 7) Positive terminal

[0163] The positive terminal can be formed in a potential range of 3 V to 4.5 V relative to the redox potential of lithium (vs. Li / Li + ) is formed of a material that is electrically stable and conductive. As the material of the positive terminal, aluminum or an aluminum alloy containing at least one element selected from the group consisting of Mg, Ti, Zn, Mn, Fe, Cu and Si can be listed. In order to reduce the contact resistance with the positive electrode collector, the positive terminal is preferably formed of the same material as the positive electrode collector.

[0164] Next, the secondary battery according to the embodiment will be described in more detail with reference to the drawings.

[0165] Figure 6 This is a cross-sectional view schematically showing an example of a secondary battery. Figure 7 Yes Figure 6 : This is an enlarged cross-sectional view of portion A of the secondary battery shown in FIG.

[0166] Figure 6 and Figure 7 The secondary battery 100 shown in FIG. Figure 6 The bag-shaped outer packaging member 2 shown in Figure 6 and Figure 7 The electrode group 1 shown in FIG. 1 and the electrolyte (not shown) are accommodated in a bag-shaped outer packaging member 2. The electrolyte (not shown) is retained in the electrode group 1.

[0167] The bag-like outer package member 2 is made of a laminate film including two resin layers and a metal layer sandwiched therebetween.

[0168] like Figure 6 As shown in FIG. 1 , the electrode group 1 is a flat wound electrode group. Figure 7 As shown in FIG. 1 , the negative electrode 3 , the separator 4 and the positive electrode 5 are included. The separator 4 is interposed between the negative electrode 3 and the positive electrode 5 .

[0169] The negative electrode 3 includes a negative electrode current collector 3a and a negative electrode active material layer 3b. The negative electrode 3 is located at the outermost portion of the wound electrode group 1. Figure 7 As shown in FIG. 1 , the negative electrode active material containing layer 3 b is formed only on the inner surface side of the negative electrode current collector 3 a. In the other parts of the negative electrode 3 , the negative electrode active material containing layer 3 b is formed on both surfaces of the negative electrode current collector 3 a.

[0170] The positive electrode 5 includes a positive electrode current collector 5 a and positive electrode active material containing layers 5 b formed on both surfaces thereof.

[0171] like Figure 6 As shown in , the negative terminal 6 and the positive terminal 7 are located near the outer peripheral end of the wound electrode group 1. The negative terminal 6 is connected to the outermost portion of the negative electrode collector 3a. In addition, the positive terminal 7 is connected to the outermost portion of the positive electrode collector 5a. These negative terminals 6 and positive terminals 7 extend to the outside from the opening of the bag-like outer packaging member 2. A thermoplastic resin layer is provided on the inner surface of the bag-like outer packaging member 2, and the opening is sealed by heat-melting bonding.

[0172] The secondary battery of the embodiment is not limited to Figure 6 and Figure 7 The secondary battery of the structure shown in FIG. 1 may also be Figure 8 and Fig. 9 A battery having the construction shown in .

[0173] Figure 8 It is a partially cutaway perspective view schematically showing another example of a secondary battery. Fig. 9 Yes Figure 8 : This is an enlarged cross-sectional view of portion B of the secondary battery shown in FIG.

[0174] Figure 8 and Fig. 9 The secondary battery 100 shown in FIG. Figure 8 and Fig. 9 The electrode group 1 shown in Figure 8 The outer packaging member 2 shown in the figure and the electrolyte not shown in the figure. The electrode group 1 and the electrolyte are accommodated in the outer packaging member 2. The electrolyte is retained in the electrode group 1.

[0175] The outer package member 2 is made of a laminate film including two resin layers and a metal layer sandwiched therebetween.

[0176] Electrode group 1 Fig. 9 The stacked electrode group 1 has a structure in which negative electrodes 3 and positive electrodes 5 are alternately stacked with separators 4 interposed therebetween.

[0177] The electrode group 1 includes a plurality of negative electrodes 3. Each of the plurality of negative electrodes 3 includes a negative electrode current collector 3a and a negative electrode active material-containing layer 3b carried on both surfaces of the negative electrode current collector 3a. In addition, the electrode group 1 includes a plurality of positive electrodes 5. Each of the plurality of positive electrodes 5 includes a positive electrode current collector 5a and a positive electrode active material-containing layer 5b carried on both surfaces of the positive electrode current collector 5a.

[0178] The negative electrode current collector 3a of each negative electrode 3 includes a portion on one side thereof where no negative electrode active material layer 3b is supported on any surface. This portion functions as a negative electrode current collector tab 3c. Fig. 9 As shown in FIG. 1 , the negative electrode collector tab 3 c does not overlap with the positive electrode 5 . In addition, the plurality of negative electrode collector tabs 3 c are electrically connected to a strip-shaped negative electrode terminal 6 . The front end of the strip-shaped negative electrode terminal 6 is led out of the outer packaging member 2 .

[0179] In addition, although not shown, the positive electrode current collector 5a of each positive electrode 5 includes a portion on one side thereof that does not carry the positive electrode active material layer 5b on any surface. This portion functions as a positive electrode collector tab. The positive electrode collector tab does not overlap with the negative electrode 3 in the same manner as the negative electrode collector tab 3c. In addition, the positive electrode collector tab is located on the opposite side of the electrode group 1 relative to the negative electrode collector tab 3c. The positive electrode collector tab is electrically connected to the strip-shaped positive terminal 7. The front end of the strip-shaped positive terminal 7 is located on the opposite side to the negative terminal 6 and is led out to the outside of the outer packaging member 2.

[0180] The secondary battery of the third embodiment includes the active material of the first embodiment. Therefore, the secondary battery has high output performance and excellent life performance.

[0181] (Fourth embodiment)

[0182] According to a fourth embodiment, there is provided a battery pack including a plurality of secondary batteries according to the third embodiment.

[0183] In the battery pack, the single cells may be electrically connected in series or in parallel, or may be arranged in a combination of series connection and parallel connection.

[0184] Next, an example of a battery assembly according to an embodiment will be described with reference to the drawings.

[0185] Fig.10 This is a perspective view schematically showing an example of a battery pack. Fig.10 The assembled battery 200 shown in FIG. 1 includes five single cells 100 a to 100 e , four bus bars 21 , a positive electrode lead 22 , and a negative electrode lead 23 . Each of the five single cells 100 a to 100 e is a secondary battery according to the third embodiment.

[0186] The bus bar 21 connects, for example, the negative terminal 6 of one cell 100a to the positive terminal 7 of the adjacent cell 100b. In this way, five cells 100 are connected in series via four bus bars 21. That is, Fig.10 The assembled battery 200 is a battery assembly of five connected in series. Although not shown in the figure, in an assembled battery including a plurality of cells electrically connected in parallel, for example, a plurality of negative terminals are connected to each other through a bus bar, and a plurality of positive terminals are connected to each other through a bus bar, so that the plurality of cells can be electrically connected.

[0187] The positive electrode terminal 7 of at least one of the five cells 100a to 100e is electrically connected to the positive electrode lead 22 for external connection. The negative electrode terminal 6 of at least one of the five cells 100a to 100e is electrically connected to the negative electrode lead 23 for external connection.

[0188] The assembled battery of the fourth embodiment includes the secondary battery of the third embodiment. Therefore, the assembled battery has high output performance and excellent life performance.

[0189] (Fifth embodiment)

[0190] According to a fifth embodiment, a battery pack is provided. The battery pack includes the assembled battery of the fourth embodiment. The battery pack may include a single secondary battery of the third embodiment instead of the assembled battery of the fourth embodiment.

[0191] The battery pack may further include a protection circuit. The protection circuit has a function of controlling the charge and discharge of the secondary battery. Alternatively, a circuit included in a device (e.g., electronic equipment, automobile, etc.) that uses the battery pack as a power source may be used as a protection circuit for the battery pack.

[0192] In addition, the battery pack may further include an external terminal for power supply. The external terminal for power supply is a component for outputting current from the secondary battery to the outside and / or for inputting current from the outside to the secondary battery. In other words, when the battery pack is used as a power source, the current is supplied to the outside via the external terminal for power supply. In addition, when the battery pack is charged, the charging current (including regenerative energy of the power of the car, etc.) is supplied to the battery pack via the external terminal for power supply.

[0193] Next, an example of a battery pack according to an embodiment will be described with reference to the drawings.

[0194] Fig.11 This is an exploded perspective view schematically showing an example of a battery pack. Fig.12 Yes means Fig.11 A block diagram of an example of a circuit of a battery pack is shown in FIG.

[0195] Fig.11 and Fig.12 The battery pack 300 shown in FIG. 1 includes a storage container 31 , a cover 32 , a protective sheet 33 , a battery module 200 , a printed wiring board 34 , wirings 35 , and an insulating plate (not shown).

[0196] Fig.11 The storage container 31 shown in the figure is a bottomed square container having a rectangular bottom surface. The storage container 31 is configured to be able to accommodate a protective sheet 33, a battery pack 200, a printed circuit wiring substrate 34, and wiring 35. The cover 32 has a rectangular shape. The cover 32 covers the storage container 31 to accommodate the battery pack 200 and the like. Although not shown in the figure, the storage container 31 and the cover 32 are provided with an opening or a connection terminal for connection with an external device and the like.

[0197] The assembled battery 200 includes a plurality of unit cells 100 , a positive electrode lead 22 , a negative electrode lead 23 , and an adhesive tape 24 .

[0198] At least one of the plurality of cells 100 is the secondary battery of the third embodiment. Fig.12 The plurality of cells 100 may be electrically connected in series as shown in . The plurality of cells 100 may be electrically connected in parallel, or may be connected in combination of series connection and parallel connection. If the plurality of cells 100 are connected in parallel, the battery capacity increases compared to the case of series connection.

[0199] The adhesive tape 24 tightly binds the plurality of cells 100. Instead of the adhesive tape 24, a heat shrink tape may be used to fix the plurality of cells 100. In this case, the protective sheets 33 are arranged on both sides of the battery pack 200, and the heat shrink tape is wound around and then thermally shrunk to bind the plurality of cells 100.

[0200] One end of the positive electrode lead 22 is connected to the assembled battery 200. One end of the positive electrode lead 22 is electrically connected to the positive electrode of one or more cells 100. One end of the negative electrode lead 23 is connected to the assembled battery 200. One end of the negative electrode lead 23 is electrically connected to the negative electrode of one or more cells 100.

[0201] The printed wiring board 34 is provided along one short side of the inner side of the container 31. The printed wiring board 34 includes a positive side connector 342, a negative side connector 343, a thermistor 345, a protection circuit 346, wirings 342a and 343a, an external terminal 350 for power supply, a positive side wiring (positive side wiring) 348a, and a negative side wiring (negative side wiring) 348b. One main surface of the printed wiring board 34 faces one side surface of the battery pack 200. An insulating plate (not shown) is interposed between the printed wiring board 34 and the battery pack 200.

[0202] The other end 22 a of the positive electrode lead 22 is electrically connected to the positive electrode connector 342 . The other end 23 a of the negative electrode lead 23 is electrically connected to the negative electrode connector 343 .

[0203] The thermistor 345 is fixed to one main surface of the printed wiring board 34. The thermistor 345 detects the temperature of each of the cells 100 and sends the detection signal to the protection circuit 346.

[0204] The external terminals 350 for power supply are fixed to the other main surface of the printed wiring board 34. The external terminals 350 for power supply are electrically connected to a device existing outside the battery pack 300. The external terminals 350 for power supply include a positive terminal 352 and a negative terminal 353.

[0205] The protection circuit 346 is fixed to the other main surface of the printed wiring substrate 34. The protection circuit 346 is connected to the positive terminal 352 via the positive side wiring 348a. The protection circuit 346 is connected to the negative terminal 353 via the negative side wiring 348b. In addition, the protection circuit 346 is electrically connected to the positive side connector 342 via the wiring 342a. The protection circuit 346 is electrically connected to the negative side connector 343 via the wiring 343a. Furthermore, the protection circuit 346 is electrically connected to each of the plurality of cells 100 via the wiring 35.

[0206] The protection sheet 33 is disposed on both inner side surfaces in the longitudinal direction of the container 31 and on the inner side surface in the transverse direction facing the printed wiring board 34 via the battery module 200. The protection sheet 33 is formed of, for example, resin or rubber.

[0207] The protection circuit 346 controls the charge and discharge of the plurality of cells 100. In addition, based on a detection signal sent from the thermistor 345 or a detection signal sent from each cell 100 or the assembled battery 200, the protection circuit 346 cuts off the electrical connection between the protection circuit 346 and the external terminals 350 (positive terminal 352, negative terminal 353) for powering an external device.

[0208] As the detection signal sent by the thermistor 345, for example, a signal that detects that the temperature of the single cell 100 is above a predetermined temperature can be listed. As the detection signal sent by each single cell 100 or the assembled battery 200, for example, a signal that detects overcharge, overdischarge, and overcurrent of the single cell 100 can be listed. When detecting overcharge, etc. of each single cell 100, the battery voltage can be detected, and the positive electrode potential or the negative electrode potential can also be detected. In the latter case, a lithium electrode used as a reference electrode is inserted into each single cell 100.

[0209] It should be noted that as the protection circuit 346 , a circuit included in a device (for example, an electronic device, a car, etc.) that uses the battery pack 300 as a power source may be used.

[0210] In addition, the battery pack 300 has the external terminal 350 for power supply as described above. Therefore, the battery pack 300 can output the current from the assembled battery 200 to the external device via the external terminal 350 for power supply, and input the current from the external device into the assembled battery 200. In other words, when the battery pack 300 is used as a power source, the current from the assembled battery 200 is supplied to the external device via the external terminal 350 for power supply. In addition, when the battery pack 300 is charged, the charging current from the external device is supplied to the battery pack 300 via the external terminal 350 for power supply. When the battery pack 300 is used as a vehicle-mounted battery, the regenerative energy of the power of the vehicle can be used as the charging current from the external device.

[0211] It should be noted that the battery pack 300 may also include a plurality of battery assemblies 200. In this case, the plurality of battery assemblies 200 may be connected in series, in parallel, or in combination of series connection and parallel connection. In addition, the printed wiring substrate 34 and the wiring 35 may also be omitted. In this case, the positive electrode side lead 22 and the negative electrode side lead 23 may also be used as the positive side terminal 352 and the negative side terminal 353 of the external terminal 350 for power supply, respectively.

[0212] Such a battery pack is used, for example, for applications requiring excellent cycle performance when a large current is taken out. Specifically, the battery pack is used, for example, as a power source for electronic equipment, a stationary battery, or a vehicle-mounted battery for various vehicles. Examples of electronic equipment include digital cameras. The battery pack is particularly suitable for use as a vehicle-mounted battery.

[0213] The battery pack of the fifth embodiment includes the secondary battery of the third embodiment or the assembled battery of the fourth embodiment. Therefore, the battery pack has high output performance and excellent life performance.

[0214] (Sixth Implementation Method)

[0215] According to a sixth embodiment, a vehicle is provided. The vehicle is equipped with the battery pack according to the fifth embodiment.

[0216] In the vehicle, the battery pack recovers, for example, regenerative energy of the vehicle's power. The vehicle may also include a mechanism (Regenerator) that converts the vehicle's kinetic energy into regenerative energy.

[0217] Examples of the vehicle include two-wheeled to four-wheeled hybrid electric vehicles, two-wheeled to four-wheeled electric vehicles, power-assisted bicycles, and railway vehicles.

[0218] The mounting position of the battery pack in the vehicle is not particularly limited. For example, when the battery pack is mounted in a car, the battery pack may be mounted in the engine room of the vehicle, behind the vehicle body, or under the seat.

[0219] The vehicle may also be equipped with multiple battery packs. In this case, the batteries contained in each battery pack may be electrically connected to each other in series, in parallel, or by combining series connection and parallel connection. For example, when each battery pack includes a battery pack, the battery packs may be electrically connected to each other in series, in parallel, or by combining series connection and parallel connection. Alternatively, when each battery pack includes a single battery, the batteries may be electrically connected to each other in series, in parallel, or by combining series connection and parallel connection.

[0220] Next, an example of a vehicle according to the embodiment will be described with reference to the drawings.

[0221] Fig.13 This is a partial perspective view schematically showing an example of a vehicle.

[0222] Fig.13 The vehicle 400 shown in FIG. 4 includes a vehicle body 40 and a battery pack 300 according to the fifth embodiment. Fig.13 In the example shown in FIG. 4 , the vehicle 400 is a four-wheeled automobile.

[0223] The vehicle 400 may be equipped with a plurality of battery packs 300. In this case, the batteries (eg, single batteries or assembled batteries) included in the battery pack 300 may be connected in series, in parallel, or in a combination of series connection and parallel connection.

[0224] Fig.13, the figure shows an example in which the battery pack 300 is mounted in the engine room located in front of the vehicle body 40. As described above, the battery pack 300 may also be mounted, for example, behind the vehicle body 40 or under the seat. The battery pack 300 can be used as a power source for the vehicle 400. In addition, the battery pack 300 can recover the regenerative energy of the power of the vehicle 400.

[0225] Next, refer to Fig.14 , an implementation method of the vehicle of the implementation method is described.

[0226] Fig.14 This is a diagram schematically showing an example of a control system related to an electrical system in a vehicle. Fig.14 The vehicle 400 shown in FIG. 4 is an electric vehicle.

[0227] Fig.14 The vehicle 400 shown in the figure includes a vehicle body 40, a vehicle power supply 41, a vehicle ECU (ECU: Electric Control Unit) 42 which is a higher-level control device of the vehicle power supply 41, an external terminal (a terminal for connecting to an external power supply) 43, an inverter 44 and a drive motor 45.

[0228] The vehicle 400 has a vehicle power source 41 mounted in, for example, an engine room, a rear part of a vehicle body, or under a seat. Fig.14 In the vehicle 400 shown in FIG. 1 , a mounting position of a vehicle power supply 41 is schematically shown.

[0229] The vehicle power supply 41 includes a plurality of (eg, three) battery packs 300 a , 300 b , and 300 c , a battery management unit (BMU) 411 , and a communication bus 412 .

[0230] The battery pack 300a includes a battery pack 200a and a battery pack monitoring device 301a (for example, VTM: Voltage Temperature Monitoring). The battery pack 300b includes a battery pack 200b and a battery pack monitoring device 301b. The battery pack 300c includes a battery pack 200c and a battery pack monitoring device 301c. The battery packs 300a to 300c are the same battery packs as the above-mentioned battery pack 300, and the battery packs 200a to 200c are the same battery packs as the above-mentioned battery pack 200. The battery packs 200a to 200c are electrically connected in series. The battery packs 300a, 300b, and 300c can be removed independently and can be exchanged with other battery packs 300.

[0231] Each of the assembled batteries 200a to 200c includes a plurality of cells connected in series. At least one of the plurality of cells is the secondary battery of the third embodiment. Each of the assembled batteries 200a to 200c is charged and discharged via a positive electrode terminal 413 and a negative electrode terminal 414.

[0232] The battery management device 411 communicates with the assembled battery monitoring devices 301a to 301c to collect information on voltage and temperature of each of the cells 100 included in the assembled batteries 200a to 200c included in the vehicle power supply 41. Thus, the battery management device 411 collects information on maintenance of the vehicle power supply 41.

[0233] The battery management device 411 and the assembled battery monitoring devices 301a to 301c are connected via a communication bus 412. In the communication bus 412, one set of communication lines shares a plurality of nodes (the battery management device 411 and one or more assembled battery monitoring devices 301a to 301c). The communication bus 412 is, for example, a communication bus constructed based on the CAN (Control Area Network) standard.

[0234] The assembled battery monitoring devices 301a to 301c measure the voltage and temperature of each cell constituting the assembled batteries 200a to 200c based on a command via communication from the battery management device 411. However, the temperature may be measured at multiple locations of only one assembled battery, and the temperature of all cells may not be measured.

[0235] The vehicle power supply 41 may also include an electromagnetic contactor (for example, Fig.14 4. The switch device 415 is shown in FIG. 4. The switch device 415 includes a pre-charge switch (not shown) that is turned on when charging the assembled batteries 200a to 200c and a main switch (not shown) that is turned on when the output from the assembled batteries 200a to 200c is supplied to the load. The pre-charge switch and the main switch each include a relay circuit (not shown) that is switched on or off by a signal supplied to a coil disposed near the switching element. The electromagnetic contactor such as the switch device 415 is controlled based on a control signal from the vehicle ECU 42 that controls the operation of the battery management device 411 or the vehicle 400 as a whole.

[0236] The converter 44 converts the input DC voltage into a high voltage of a three-phase alternating current (AC) for driving the motor. The three-phase output terminals of the converter 44 are connected to the three-phase input terminals of the drive motor 45. The converter 44 is controlled based on a control signal from the vehicle ECU 42 for controlling the operation of the battery management device 411 or the entire vehicle. By controlling the converter 44, the output voltage from the converter 44 is adjusted.

[0237] The drive motor 45 is rotated by the electric power supplied from the inverter 44. The driving force generated by the rotation of the drive motor 45 is transmitted to the axle and the drive wheels W via a differential gear unit, for example.

[0238] In addition, although not shown, the vehicle 400 is provided with a regenerative brake mechanism (regenerator). The regenerative brake mechanism rotates the drive motor 45 when braking the vehicle 400, converting kinetic energy into regenerative energy as electrical energy. The regenerative energy recovered by the regenerative brake mechanism is input to the converter 44 and converted into a direct current. The converted direct current is input into the vehicle power supply 41.

[0239] One terminal of the connection line L1 is connected to the negative terminal 414 of the vehicle power supply 41. The other terminal of the connection line L1 is connected to the negative input terminal 417 of the converter 44. On the connection line L1, between the negative terminal 414 and the negative input terminal 417, a current detection unit (current detection circuit) 416 in the battery management device 411 is provided.

[0240] One terminal of the connection line L2 is connected to the positive terminal 413 of the vehicle power supply 41. The other terminal of the connection line L2 is connected to the positive input terminal 418 of the converter 44. A switch device 415 is provided between the positive terminal 413 and the positive input terminal 418 on the connection line L2.

[0241] The external terminal 43 is connected to the battery management device 411. The external terminal 43 can be connected to an external power source, for example.

[0242] The vehicle ECU 42 responds to the operation input of the driver and the like and coordinates with other management devices and control devices including the battery management device 411 to control the vehicle power supply 41, the switch device 415, the inverter 44, etc. Through the coordinated control of the vehicle ECU 42 and the like, the output of the power from the vehicle power supply 41 and the charging of the vehicle power supply 41 are controlled, and the overall management of the vehicle 400 is performed. Data on the maintenance of the vehicle power supply 41, such as the remaining capacity of the vehicle power supply 41, is transmitted between the battery management device 411 and the vehicle ECU 42 through the communication line.

[0243] The vehicle of the sixth embodiment is equipped with the battery pack of the fifth embodiment. Therefore, the vehicle has high performance and high reliability.

[0244] Example

[0245] Hereinafter, examples will be described.

[0246] (Example 1)

[0247] <Synthesis of Active Substance>

[0248] First, prepare commercially available oxide reagents, namely Nb2O5 and TiO2. Weigh these powders so that the molar ratio of Nb / Ti becomes 1.0. Furthermore, add Na2SO4 so that the molar ratio of Nb / S becomes 1:0.1. Mix them using a ball mill for 1 hour. The resulting mixture is placed in an electric furnace and subjected to temporary calcination at a temperature of 1000°C for 12 hours. The powder after temporary calcination is placed in a ball mill again and mixed for 1 hour. The mixture is placed in an electric furnace again, and the first formal calcination is performed at a temperature of 1100°C for 5 hours. After cooling to room temperature, it is pulverized using a ball mill for 1 hour, and the second formal calcination is performed at a temperature of 1100°C for 5 hours. The taken-out powder is strongly pulverized using a hammer mill and a roller compressor, and pulverized using a wet ball mill for 3 hours. The obtained powder is placed in an electric furnace in which the temperature in the furnace has been raised to 1100°C in advance, and reheated for 1 hour. Thereafter, the powder was quickly taken out of the electric furnace and placed in liquid nitrogen for cooling. In this way, the active material powder according to Example 1 was obtained.

[0249] <Negative electrode production>

[0250] Acetylene black (AB) as a conductive agent is mixed with 10 parts by weight relative to 100 parts by weight of the above-mentioned active material powder. The mixture is dispersed in NMP (N-methyl-2-pyrrolidone), and polyvinylidene fluoride (PVdF) as a binder is mixed with 10 parts by weight relative to 100 parts by weight of the active material powder to prepare an electrode slurry. By applying the slurry on a collector made of aluminum foil and drying it, an electrode having an active material layer coated on both sides of the aluminum foil is obtained. The obtained electrode is compacted using a roller pressing device at a specified pressing pressure to obtain an electrode density of 2.3g / cm 3 Next, the negative electrode was punched out so that the electrode area including the active material layer would be 100 mm×80 mm.

[0251] <Positive electrode production>

[0252] Instead of synthesized active material powder, LiNi 0.5 Co 0.2 Mn 0.3 O2 was used as the positive electrode active material, and the electrode was prepared with the same mixing ratio of AB and PVdF as the negative electrode, and the electrode density was 2.6 g / cm 3 Next, the positive electrode was punched out so that the electrode area including the active material layer would be 100 mm×80 mm.

[0253] <Battery Production>

[0254] Next, the positive electrode, one separator, negative electrode, and another separator prepared above were repeatedly stacked in this order to obtain a laminated body. The laminated body was heated and pressed at 90° C. to prepare an electrode group with a thickness of 2.0 mm.

[0255] The positive and negative terminals were connected to the obtained electrode group. Next, the electrode group was placed in a bag made of a laminate film and vacuum dried at 80° C. for 24 hours. The laminate film was composed of polypropylene layers formed on both sides of an aluminum foil with a thickness of 40 μm, and the overall thickness was 0.1 mm.

[0256] A liquid non-aqueous electrolyte was injected into the bag containing the laminated film of the electrode group as before. As the liquid non-aqueous electrolyte, a solution obtained by dissolving LiPF6 as an electrolyte salt at a concentration of 1M in a mixed solution obtained by mixing propylene carbonate (PC) and diethyl carbonate (DEC) at a volume ratio of 1:1 was used. Thereafter, the bag was completely sealed by heat sealing. In this way, a non-aqueous electrolyte battery with a width of 110 mm, a length of 85 mm, and a thickness of 2.2 mm was produced.

[0257] The non-aqueous electrolyte battery produced was charged and discharged in the range of 25%-75% of the depth of charge (DOD). The charge and discharge current value was set to 0.2C (hourly discharge rate), and the 0.2C discharge capacity was confirmed at room temperature. The value of the 0.2C discharge capacity becomes an indicator of energy density. The capacity of the non-aqueous electrolyte battery produced in Example 1 is 2000mAh.

[0258] (Example 2)

[0259] The amount of Na2SO4 added was changed so that the molar ratio of Nb / S became 1:0.5. Except for this point, the active material powder was synthesized by the same method as described in Example 1, and the active material powder was used for the negative electrode to produce a non-aqueous electrolyte battery.

[0260] (Example 3)

[0261] The amount of Na2SO4 added was changed so that the molar ratio of Nb / S became 1:1. Except for this point, the active material powder was synthesized by the same method as described in Example 1, and the active material powder was used for the negative electrode to produce a non-aqueous electrolyte battery.

[0262] (Example 4)

[0263] On the basis of Na2SO4, K3PO4 was added in such a way that the molar ratio of Nb / P became 1:0.1. Except for this, the active material powder was synthesized by the same method as described in Example 1, and the active material powder was used for the negative electrode to produce a non-aqueous electrolyte battery.

[0264] (Comparative Example 1)

[0265] An active material powder was synthesized by the same method as described in Example 1 except that Na 2 SO 4 was not added as a flux, and the active material powder was used for a negative electrode to produce a nonaqueous electrolyte battery.

[0266] (Comparative Example 2)

[0267] The active material powder was synthesized in the same manner as in Example 1 except that FePO 4 was added instead of Na 2 SO 4 so that the molar ratio of Nb / P became 1:0.5, and the active material powder was used for the negative electrode to produce a nonaqueous electrolyte battery.

[0268] (Comparative Example 3)

[0269] An active material powder was synthesized in the same manner as in Example 1 except that KCl was added instead of Na 2 SO 4 so that the molar ratio of Nb / K became 1:0.5, and the active material powder was used for a negative electrode to produce a nonaqueous electrolyte battery.

[0270] (Comparative Example 4)

[0271] An active material powder was synthesized by the same method as described in Example 1 except that the temperature of the reheat treatment was changed to 1400° C., and the active material powder was used for a negative electrode to produce a nonaqueous electrolyte battery.

[0272] <Powder X-ray Diffraction Measurement>

[0273] The active material powder synthesized in each example was subjected to diffraction pattern analysis by the method described in the first embodiment and analyzed by the Rietveld method. The crystallite diameter was investigated from the obtained diffraction lines. Table 1 shows the crystallite diameter of the active material powder in each example.

[0274] <Measurement of Neck Shrinkage Ratio N>

[0275] For the active material powder synthesized in each example, the total perimeter L of the primary particles and the sum L of the perimeters of the primary particles excluding the constricted portion were measured using the image analysis tool ImageJ according to the method described in the first embodiment. cl The relationship between cl ) / L. In addition, assuming that the cross section of the active material particle is a perfect circle, the average particle diameter D is calculated from the total number of particles n observed and the total circumference L (D=L / nπ). The results are shown in Table 1.

[0276] <Confirmation of impurity elements>

[0277] The active material powder synthesized in each example was checked for the presence or absence of impurities in the necking portion of the grain boundary between crystallites according to the method described in the first embodiment.

[0278] <Battery Performance Evaluation>

[0279] For the non-aqueous electrolyte batteries prepared in Examples 1-4 and Comparative Examples 1-4, as an indicator of rapid discharge performance, discharge was performed at 10C to obtain the discharge capacity ratio relative to the 0.2C capacity. In addition, in order to confirm that stable charge and discharge can be performed, each non-aqueous electrolyte battery was repeatedly charged and discharged for 5000 cycles (charging and discharging was set as 1 cycle), and the discharge capacity retention rate after 5000 cycles was investigated. Repeated charging and discharging was performed at 45°C within the range of depth of charge (DOD) 25%-75%, with the current value during charging set to 10C (hourly discharge rate) and the current value during discharging set to 10C (hourly discharge rate). In order to confirm the discharge capacity retention rate after 5000 times, charge and discharge were performed again at 0.2C (hourly discharge rate), and the capacity retention rate (%) when the initial discharge capacity was set to 100% was calculated by dividing the discharge capacity after 5000 times by the initial discharge capacity and multiplying by 100. This capacity retention rate becomes an indicator of long-life performance. The above results are summarized in Table 1.

[0280] Table 1

[0281]

[0282] As shown in Table 1, for the active materials synthesized in Examples 1-4, the necking ratio N falls within the range of more than 0.1 and less than 0.6. In contrast, for Comparative Example 1, the ratio N becomes 0.1, and for Comparative Examples 2-4, the ratio N exceeds 0.6. The non-aqueous electrolyte battery using the active materials involved in Examples 1-4 for the negative electrode shows high rapid discharge performance (10C / 0.2C capacity ratio) and cycle life performance (discharge capacity retention rate after 5000 times) compared with the battery using the active materials involved in Comparative Examples 1-4.

[0283] According to at least one embodiment described above, an active material is provided. The active material includes secondary particles, the secondary particles including a plurality of primary particles containing niobium oxide. The secondary particles include adjacent portions of the primary particles adjacent to each other and a constricted portion formed by the primary particles being joined to each other. The sum of the total perimeter L of the primary particles and the perimeter L of the primary particles excluding the constricted portion is cl Satisfy 0.1<(LL cl) / L≤0.6. If the active material is used, it is possible to provide an electrode for a secondary battery having high output performance and excellent life performance, a secondary battery and a battery pack having high output performance and excellent life performance, and a vehicle having the battery pack.

[0284] Several embodiments of the present invention have been described, but these embodiments are presented as examples and are not intended to limit the scope of the invention. These novel embodiments can be implemented in various other ways, and various omissions, substitutions, and changes can be made without departing from the scope of the subject matter of the invention. These embodiments and their variations are included in the scope and subject matter of the invention, and are also included in the invention described in the claims and their equivalents.

[0285] It should be noted that the above-mentioned implementation methods can be summarized in the following technical solutions.

[0286] (Technical Solution 1) An active material comprising secondary particles,

[0287] The secondary particles include a plurality of primary particles containing niobium oxide.

[0288] The secondary particles include adjacent portions where the primary particles are adjacent to each other and constricted portions where the primary particles are bonded to each other.

[0289] The total perimeter L of the primary particle and the sum of the perimeters of the primary particle excluding the neck portion L cl Satisfy 0.1<(LL cl ) / L≤0.6.

[0290] (Technical Solution 2)

[0291] According to the above-mentioned technical solution 1, the diameter of the crystallite of the above-mentioned niobium oxide is greater than 10nm and less than 300nm, the average particle size of the above-mentioned primary particles is in the range of greater than 0.5μm and less than 3μm, and grain boundaries containing niobium and one or more elements selected from the group consisting of P, K, and Fe are formed between the crystallites in the same way as the parent phase.

[0292] (Technical Solution 3)

[0293] According to the above-mentioned technical solution 2, the concentration of the above-mentioned element in the above-mentioned grain boundary is higher than the concentration in the above-mentioned parent phase by 20% or more.

[0294] (Technical Solution 4)

[0295] An electrode comprising the active material according to any one of the above technical solutions 1 to 3.

[0296] (Technical Solution 5)

[0297] According to the above technical solution 4, the above electrode includes an active material-containing layer containing the above active material.

[0298] (Technical Solution 6) A secondary battery, comprising:

[0299] positive electrode,

[0300] A negative electrode including a negative electrode active material, and

[0301] Electrolytes,

[0302] The negative electrode active material includes secondary particles, the secondary particles include a plurality of primary particles containing niobium oxide, the secondary particles include first adjacent portions where the primary particles are adjacent to each other and second adjacent portions where the primary particles are in contact with each other via interfaces.

[0303] The total perimeter L of the primary particle and the sum of the perimeters of the primary particle excluding the second adjacent portion L cl Satisfy 0.1≤(LL cl ) / L≤0.6.

[0304] (Technical Solution 7)

[0305] A battery pack comprises the secondary battery described in technical solution 6 above.

[0306] (Technical Solution 8)

[0307] According to the above technical solution 7, it further includes an external terminal for power supply and a protection circuit.

[0308] (Technical Solution 9)

[0309] According to the technical solution 7 or 8, it comprises a plurality of the above-mentioned secondary batteries, and the above-mentioned secondary batteries are electrically connected in series, in parallel, or in a combination of series and parallel.

[0310] (Technical Solution 10)

[0311] A vehicle equipped with the battery pack according to any one of the above technical solutions 7 to 9.

[0312] (Technical Solution 11)

[0313] According to the above technical solution 10, it includes a mechanism for converting the kinetic energy of the above vehicle into regenerative energy.

Claims

1. An active material comprising secondary particles, the secondary particles comprising a plurality of primary particles containing niobium oxide, The secondary particles include adjacent portions where the primary particles are adjacent to each other and constricted portions where the primary particles are bonded to each other. The sum L of the total perimeter L of the primary particle and the perimeter L of the primary particle excluding the constricted portion cl Satisfy 0.1<(LL cl ) / L≤0.

6.

2. The active material according to claim 1, wherein The crystallite diameter of the niobium oxide is greater than 10 nm and less than 300 nm, the average particle size of the primary particles is within the range of greater than 0.5 μm and less than 3 μm, and grain boundaries containing niobium and one or more elements selected from the group consisting of P, K, and Fe are formed between the crystallites in the same manner as the parent phase.

3. The active material according to claim 2, wherein The concentration of the element in the grain boundary is higher than that in the parent phase by 20% or more. 4 . An electrode comprising the active material according to claim 1 .

5. The electrode according to claim 4, wherein The electrode includes an active material-containing layer containing the active material.

6. A secondary battery comprising: positive electrode, A negative electrode including a negative electrode active material, and Electrolytes, The negative electrode active material includes secondary particles, the secondary particles include a plurality of primary particles containing niobium oxide, the secondary particles include first adjacent portions where the primary particles are adjacent to each other and second adjacent portions where the primary particles are in contact with each other via interfaces. The sum L of the total perimeter L of the primary particle and the perimeter L of the primary particle excluding the second adjacent portion cl Satisfy 0.1≤(LL cl ) / L≤0.

6. 7 . A battery pack comprising the secondary battery according to claim 6 .

8. The battery pack according to claim 7, wherein: Further including: External terminals for power supply, and Protection circuit.

9. The battery pack according to claim 7 or 8, wherein: A plurality of the secondary batteries are provided, The secondary batteries are electrically connected in series, in parallel, or in a combination of series and parallel. 10 . A vehicle equipped with the battery pack according to claim 7 .

11. The vehicle according to claim 10, wherein: A mechanism is included for converting the kinetic energy of the vehicle into regenerative energy.